Mendalamkan Spiritualitas dan Meluaskan Intelektualitas: Kajian Tematik dalam al-Quran - Dicky Adi setiawan, Dicky; Imam Bashori, Bashori (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2021)
As times goes by, the reality of the world grew more rapidly. As period gets older, the technology also get longer more advanced. Advance in technology certainly make the majority of millennials become lazy to read. This reality is proven to be among Indonesian millennial generation, namely from the many syndromes playing games both offline and online. The rapid development of the world technology with all its features pamper young people more often open social media than reading books. As a result, intellectuality appears to be declining. On the other side, there is prioritize intellectual than spiritual. Here the author will examine how the message of the Qur'an will strive for between spirituality and intellectuality simultaneously, especially in this millennial era. In this study, the type of research use qualitative descriptive where the purpose of this study is to present events or facts, circumstances, phenomena, variables and circumstances that occur during the study by presenting what actually happened. The result of this study is in improving spiritual and intellectual in this millennial era, by implication it is necessary to smoothen 3 things, there are: 1. With Faith 2. Increase all good deeds to Allah 3. Always increase the pieties. These three concepts are expected to deepen spiritually and improve intellectually in this millennial era